The teaching of emotions and beliefs to students with autism spectrum disorders: Collaborative research - Lozano Martínez, Josefina; Alcaraz García, sal; Colás Bravo, Pilar (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This study reports the effect of the development of an educational intervention in student with autism spectrum disorders (ASD) on the understanding of emotions and beliefs as way for the improvement of their social skills. For it, twelve students with ASD of Primary and Secondary Education took part in a design of collaborative research with initial and final evaluation where, for the obtaining of information, didactic materials were elaborated for the education and evaluation of the understanding of emotions and beliefs and a scale of valuation of emotional and social skills for persons with ASD (EVHES), before validated. The results show that the development of collaborative methods between students’ teachers with ASD and university specialists affects positively on the processes of education of the understanding of emotions and beliefs and improvement of the social skills.